2018
DOI: 10.1002/aenm.201703659
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Interfacial Engineering by Bismuth Modification for Efficient and Thermoresistant Perovskite Solar Cells

Abstract: Organic–inorganic halide perovskite solar cells (PSCs) have emerged as attractive alternatives to conventional solar cells. It is still a challenge to obtain PSCs with good thermal stability and high permanence, especially at extreme outdoor temperatures. This work systematically studies the effects of Bi3+ modification on structural, electrical, and optical properties of perovskite films (FA0.83MA0.17Pb(I0.83Br0.17)3) and the performance of corresponding PSCs. The results indicate that Bi3+ modified PSCs can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 67 publications
(158 reference statements)
2
68
1
Order By: Relevance
“…In the past, tremendous efforts have contributed to investigate partial replacement of Pb 2+ (ion radius: 1.49 Å) by Sn 2+ (ion radius: 1.35 Å) for the purpose of extending the absorption onset and reducing toxicity of lead . Although the absorption spectrum is much extended, the device based on Sn suffers from poor chemical stability due to oxidation of Sn 2+ to Sn 4+ in the presence of oxygen and moreover poor PCE because of fast electron/hole recombination . Encouraged by both development of lead‐free or lead‐less perovskite, other (transition) metal ions were also employed to partially substitute Pb 2+ .…”
Section: Control Of Recombination In the Bulk Perovskitementioning
confidence: 99%
See 1 more Smart Citation
“…In the past, tremendous efforts have contributed to investigate partial replacement of Pb 2+ (ion radius: 1.49 Å) by Sn 2+ (ion radius: 1.35 Å) for the purpose of extending the absorption onset and reducing toxicity of lead . Although the absorption spectrum is much extended, the device based on Sn suffers from poor chemical stability due to oxidation of Sn 2+ to Sn 4+ in the presence of oxygen and moreover poor PCE because of fast electron/hole recombination . Encouraged by both development of lead‐free or lead‐less perovskite, other (transition) metal ions were also employed to partially substitute Pb 2+ .…”
Section: Control Of Recombination In the Bulk Perovskitementioning
confidence: 99%
“…Although the absorption spectrum is much extended, the device based on Sn suffers from poor chemical stability due to oxidation of Sn 2+ to Sn 4+ in the presence of oxygen and moreover poor PCE because of fast electron/hole recombination . Encouraged by both development of lead‐free or lead‐less perovskite, other (transition) metal ions were also employed to partially substitute Pb 2+ . Although In 3+ is somewhat difficult to replace in part Pb 2+ due to charge imbalance, excess charge was tried to compensate by adding additional anion such as Cl, leading to MAPb 1− x In x I 3 Cl x , which was applied in inverted planar PSCs (Table ).…”
Section: Control Of Recombination In the Bulk Perovskitementioning
confidence: 99%
“…The retarded recombination was also manifested by the lower dark current density as illustrated in Fig. S6, which indicated that the Nb 5+ doping in SnO 2 could reduce the energy loss caused by the non-radiative recombination, resulting in the enhanced FF and V OC [42,43]. Thus, we concluded two aspects responsible for the enhanced devices performance.…”
Section: Resultsmentioning
confidence: 67%
“…[38] The crystallinity,e lectron extraction and structural stability of FAI 0.83 MA 0.17 Pb(I 0.83 Br 0.17 ) 3 perovskite film can be significantly improvedb ya dding MA 3 Bi 2 Br 9 into the precursor solution ( Figure 17). [39] The enhanced PCE of the MA 3 Bi 2 Br 9 -modified device was ascribed to reduced lattice defects, enlarged grain size, and increased electron extraction efficiency. Therefore, the incorporation of Bi 3 + in 3D Pb-based perovskites is promising approachtoi mprove the efficiency and stability of PSCs.…”
Section: Bi Doping In Pristine Perovskite Materials and Pscsmentioning
confidence: 95%
“…The 2 D MA 3 Bi 2 I 9 /3 D MAPbI 3 heterostructured PSCs exhibited a high PCE of 19.87 % along with reduced hysteresis and improved air stability, combining the advantages of the high‐performance of MAPbI 3 and the stability of MA 3 Bi 2 I 9 (Figure ) . The crystallinity, electron extraction and structural stability of FAI 0.83 MA 0.17 Pb(I 0.83 Br 0.17 ) 3 perovskite film can be significantly improved by adding MA 3 Bi 2 Br 9 into the precursor solution (Figure ) . The enhanced PCE of the MA 3 Bi 2 Br 9 ‐modified device was ascribed to reduced lattice defects, enlarged grain size, and increased electron extraction efficiency.…”
Section: Bi Doping In Pristine Perovskite Materials and Pscsmentioning
confidence: 99%